Mosla Chinensis Extract Enhances Growth Performance, Antioxidant Capacity, and Intestinal Health in Broilers by Modulating Gut Microbiota - Wei Wang; Yuyu Wang; Peng Huang; Junjuan Zhou; Guifeng Tan; Jianguo Zeng; Wei Liu (Microorganisms)
This study aimed to evaluate the effects of Mosla chinensis extract (MCE) on broiler intestinal health. A total of 240 1-day-old Arbor Acres (AA) broilers (balanced for sex) were randomly allocated into four treatment groups, each with six replicates of 10 chickens. The study comprised a starter phase (days 1–21) and a grower phase (days 22–42). The control group (C) received a basal diet, while the experimental groups were supplemented with low (S1, 500 mg/kg), medium (S2, 1000 mg/kg), and high doses (S3, 2000 mg/kg) of MCE. The results showed that MCE supplementation significantly improved average daily gain in broilers (p < 0.05) and reduced the feed-to-gain ratio in broilers. Additionally, MCE enhanced the anti-inflammatory and antioxidant capacity of broilers. In the duodenum and cecum, MCE significantly upregulated the expression of tight junction proteins Claudin-1, and Occludin, with the high-dose group showing the strongest effect on intestinal barrier protection (p < 0.05). There was no significant difference in ZO-1 in dudenum (p > 0.05). Microbial analysis indicated that MCE supplementation significantly reduced the Chao and Sobs indices in both the small and large intestines (p < 0.05). At the same time, the Coverage index of the small intestine increased, with the high-dose group demonstrating the most pronounced effect. Beta diversity analysis revealed that MCE had a significant modulatory effect on the microbial composition in the large intestine (p < 0.05), with a comparatively smaller impact on the small intestine. Furthermore, MCE supplementation significantly increased the relative abundance of Ruminococcaceae and Alistipes in the large intestine, along with beneficial genera that promote short-chain fatty acid (SCFA) production, thus optimizing the gut microecological environment. Correlation analysis of SCFAs further confirmed a significant association between the enriched microbiota and the production of acetate, propionate, and butyrate (p < 0.05). In conclusion, dietary supplementation with MCE promotes healthy growth and feed intake in broilers and exhibits anti-inflammatory and antioxidant effects. By optimizing gut microbiota composition, enhancing intestinal barrier function, and promoting SCFA production, MCE effectively maintains gut microecological balance, supporting broiler intestinal health.